Digital vs. physical goods: Evidence from the book market - Maximilian M. Gail; Phil-Adrian Klotz (Philipps-University Marburg, School of Business and Economics, 2024)
The digitization has reshaped the multimedia industry in a tremendous way and particularly driven the transition from physical to digital goods. With respect to the book industry, Amazon reported that purchases of e-books had surpassed those of print books for the first time in 2011. The goal of this paper is to examine the substitutability between digital and print book formats in a country with fixed book prices (Germany) and a country without such regulated prices (United Kingdom). We use a unique cross-sectional data set of book prices for these two countries and exploit genre as well as publisher variation to estimate cross-format elasticities in an IV setting. We find that consumers basically consider e-books as (imperfect) substitutes for print books, even though there are country-, genre-and format-specific differences. Our results have important implications for the implementation of fixed book prices and the taxation of different book formats as well as for the release strategies of the publishers for the individual book formats.
Keywords: D12; H23; L42; L82; Z11; 330; Digital goods; e-books; cross-format elasticities; text mining; digital mediapolicy; 3SLS